Searching for new genes and loci involved in cleft lip and palate in the Polish population – genome-wide association study - Adrianna Mostowska; Kamil K. Hozyasz; Piotr Wójcicki; Barbara Biedziak; Joanna Wesoły; Anna Sowińska; Sylwia Matuszewska-Trojan; Paweł P. Jagodziński (Journal of Medical Science, 2014)
The project “Searching for new genes and loci involved in cleft lip and palate in the Polish population – genome-wide association study” is a case-control study in a group of unrelated subjects with non-syndromic cleft lip with or without cleft palate (NSCL/P) and healthy individuals with no family history of clefting or other congenital disorders. The overall goal of this grant proposal is to identify novel genetic factors, which can play a significant role in the pathogenesis of orofacial clefts in the Polish population. To accomplish the proposed aim, a two stage genome-wide association study will be performed. In the first stage, Illumina's HumanOmni Express BeadChips arrays will be used to genotype over 700,000 polymorphisms in NSCL/P patients and controls. In the second stage, SNPs showing the most compelling association with the risk of orofacial clefts will be tested in an independent sample set using standard genotyping methods. This research project is expected to be completed in July 2015.